UMUR HADIS DAN DINAMIKA SOSIAL (Kajian Terhadap Transformasi Nilai Sosial dalam Masayarakat Islam) - Imron Taslim; Muhajirin (AL-BAYAN INSTITUTE, 2024)
This study examines the dynamic interpretation of a hadith encouraging women to perform prayers in the innermost part of their homes, as part of the transformation of social values in contemporary Islamic society. Using a qualitative approach and literature review, this research explores how the age of the hadith and social context influence the reinterpretation of its social values. The findings reveal that the understanding of hadith is not static but evolves according to the socio-cultural developments within Muslim communities. This transformation reflects an ongoing dialogue between religious texts and dynamic social realities, significantly impacting women’s roles and positions in society. The study fills a gap in research regarding the relationship between hadith age and social value transformation, emphasizing the importance of contextual interpretation to address contemporary social challenges. The implications of this research are crucial for developing inclusive and adaptive religious education and strengthening religious literacy responsive to changing times.